Prevalence of Depression in Patients with Visual Impairment in Cataract: A Systematic Literature Review - Freshcilia Oktaviyani (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2021)
Introduction. Depression is a chronic and often recurrent psychiatric disorder among older people, and its association with cataracts has not been well defined. Several studies have shown that depression is a prevalent mental health problem in ophthalmological practice and is often unrecognized or untreated. A systematic review was conducted to investigate the prevalence of depression in patients with visual impairment in cataracts.Methods. A literature search was performed on PubMed and Medline in the last 10 years (2011 to 2021). The search strategy used the following terms: (prevalence) and (visual impairment or blindness) and (cataract) and (depression or depressive symptoms). Of the 544 electronics, 226 articles were selected in free full text and 10 studies were identified as being possibly relevant. Results. Depression was associated with visual impairment in all studies. The prevalence of depression is higher in patients with eye disease.Conclusion. The prevalence of depression among eye disease patients was higher than that in healthy people. Cataract surgery is associated with an improvement in depressive symptomatology. More research is needed to identify effective strategies for the prevention and management of depression in patients with cataracts or visual impairment.